2009
DOI: 10.1097/sap.0b013e3181776374
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion Dynamics of Free DIEP and SIEA Flaps During the First Postoperative Week Monitored With Dynamic Infrared Thermography

Abstract: Perfusion dynamics of 16 free DIEP flaps and 4 free SIEA flaps were studied during the first, third, and sixth postoperative day using dynamic infrared thermography (DIRT). For both flap types the zone positioned over the perforator is perfused first, followed by the adjacent ipsilateral zone, and finally the contralateral zones. Perfusion of the subdermal plexus of all zones preceded the perfusion of the subcutaneous layer of all zones. While the initial hyperemia subsided with time, the total number of hot s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 33 publications
2
56
0
4
Order By: Relevance
“…The subcutaneous tissue, however, is only well perfused after several days, when the choke vessels in this layer have dilated. 7 Despite an initial decrease in blood flow levels in some studies, all studies eventually demonstrated a relative hyperperfusion of free flaps postoperatively, confirming our results. There are several possible explanations for this observation.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The subcutaneous tissue, however, is only well perfused after several days, when the choke vessels in this layer have dilated. 7 Despite an initial decrease in blood flow levels in some studies, all studies eventually demonstrated a relative hyperperfusion of free flaps postoperatively, confirming our results. There are several possible explanations for this observation.…”
Section: Discussionsupporting
confidence: 81%
“…3 Other explanations may be an increased cardiac output as a result of the surgical procedure, declined vascular resistance due to sympathetic denervation or a compensation mechanism for higher oxygen consumption in the transplanted tissue. 7,8 In the peripheral part of the flap, there was a decrease in blood flow directly after surgery and 24 hours after reperfusion, compared with baseline flow values. This was expected, because it is known that the peripheral zone of the flap has a higher chance of necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…O stress térmico pode ser conseguido, por exemplo, com água 2 REVISÃO DE LITERATURA de imersão, ou por aplicação de objetos frios ou quentes na superfície da pele. A taxa padrão e em que a temperatura da pele recupera em direção ao seu equilíbrio é registrado com uma câmera infravermelha (WEERD et al, 2009;WEERD et al, 2011).…”
Section: Termografia E Anaplastiaunclassified
“…Pode-se então observar com o passar das semanas um padrão térmico mais homogêneo nas imagens, até que a determinação da área do retalho torne-se mais custosa por conta da similaridade térmica com a pele ao redor. (AWWAD et al, 1983;FRANCIS et al, 1979) e ser usada como ferramenta de reconhecimento precoce de deiscência da ferida cirúrgica, conforme proposto por diversos autores (SALMI et al, 1995;EICHHORN et al, 2009;WEERD et al, 2009;WEERD et al, 2011).…”
Section: Grupounclassified
See 1 more Smart Citation